Immortalization of mouse neural precursor cells by the c-myc oncogene. - Bartlett, P F (1988)
Immortalized cell lines have been generated from embryonic mouse neuroepithelium by infection with a retrovirus containing the c-myc oncogene. The morphology and the antigenic phenotype of the cloned cell lines are characteristic of normal neuroepithelium. Although the cell lines are stable and do not spontaneously differentiate, morphological changes can be induced with both acidic and basic fibroblast growth factor. Fibroblast growth factor at 5 ng/ml stimulates differentiation of the neuroepithelial cells, and it has been shown that the cloned cell line 2.3D can differentiate into astrocytes, containing glial fibrillary acidic protein, and neurons, expressing the A2B5 marker and neurofilaments. This indicates that some cells in the neuroepithelium at embryonic day 10 are multipotent and are not restricted to either the glial or neuronal cell lineage. The cell lines also can be induced with interferon gamma to express class I and class II histocompatibility antigens. The response of the c-myc-immortalized cell lines to these two factors is similar to that observed with freshly isolated neuroepithelium and suggests that such immortalized precursor populations are representative of the cells found in the developing neuroepithelium.